Nanoscale Measurement of Surface Roughness and the existing Surface Forces of Aluminum by AFM - Pun, Purna B; Lamichhane, Shobha K (Himalayan Physics, 2011)
The surface contamination affects Atomic Force Microscope (AFM) performance. Thermal agitation during mapping doping, thermal oxidation, annealing impurities and crystal defects promotes the roughness; various kinds of forces on the surface can be detected by the interaction between tip of cantilever and sample. This interaction not only help us to understand the characteristics and morphology of the sample but also useful to measure the surface force of the aluminum sample too. Key words: Atomic Force Microscope (AFM) performance; Thermal oxidation; Annealing impurities; Crystal defects The Himalayan Physics Vol.2, No.2, May, 2011 Page: 76-79 Uploaded Date: 1 August, 2011